2001
DOI: 10.1016/s0006-3495(01)75890-0
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Properties of Gel and Fluid Clusters in DMPC/DSPC Bilayers: Monte Carlo Simulation Approach Using a Two-State Model

Abstract: In this paper the geometrical properties of gel and fluid clusters of equimolar dimyristoylphosphatidylcholine/distearoylphosphatidylcholine (DMPC/DSPC) lipid bilayers are calculated by using an Ising-type model (Sugar, I. P., T. E. Thompson, and R. L. Biltonen. 1999. Biophys. J. 76:2099-2110). The model is able to predict the following properties in agreement with the respective experimental data: the excess heat capacity curves, fluorescence recovery after photobleaching (FRAP) threshold temperatures at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 72 publications
(108 reference statements)
6
36
0
Order By: Relevance
“…hydrophobic or van der Waals interactions between membrane lipids, may be programmed by incoming synaptic signals that modulate the shape of a spatially extended, fractal lipid lattice or microdomain (Bieberich, 2000a). Recently, it has been found that biological membranes exhibit requisite characteristics of fractal geometry with respect to curvature, shape, and internal molecular organization (Hoop and Peng, 2000;Rabouille et al, 1992;Sugar et al, 2001). Alternatively, microtubules or other filaments of the cytoskeleton may also form a lattice structure that can be shaped into a fractal.…”
Section: Conclusion: Rfnns and Consciousnessmentioning
confidence: 99%
“…hydrophobic or van der Waals interactions between membrane lipids, may be programmed by incoming synaptic signals that modulate the shape of a spatially extended, fractal lipid lattice or microdomain (Bieberich, 2000a). Recently, it has been found that biological membranes exhibit requisite characteristics of fractal geometry with respect to curvature, shape, and internal molecular organization (Hoop and Peng, 2000;Rabouille et al, 1992;Sugar et al, 2001). Alternatively, microtubules or other filaments of the cytoskeleton may also form a lattice structure that can be shaped into a fractal.…”
Section: Conclusion: Rfnns and Consciousnessmentioning
confidence: 99%
“…The difference of our approach from that used by Suger et al [3] and Heimburg [4] is the distribution of T c with a given Gauss type function f (T 0i ). The first term in (4) describes the chemical potential of a subsystem at the i-th site in the Ising network.…”
Section: Monte-carlo Computationsmentioning
confidence: 94%
“…We consider a two-state system in a temperature dependent field as it was introduced by Suger et al [3] and Heimburg [4]:…”
Section: Monte-carlo Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous numerical studies of the gel to fluid transition in lipid-cholesterol assemblies and the formation of superlattices have used a triangular lattice description of the membrane [15][16][17][18][19][20][21][22]. While these studies were able to capture several salient features of the thermotropic transition and even the formation of superlattices, such models cannot, obviously, capture the effects of lateral mobility of the molecules.…”
Section: Introductionmentioning
confidence: 99%